Micha Ullman. - Rattemeyer, Volker (Wiesbaden : Museum Wiesbaden, 2003)
The catalogue documents 32 projects realized by Micha Ullman over a period of 30 years. The ground sculptures exhibited in Wiesbaden are described in a separate catalogue supplement.
Public Space sculptures, Awards, Collections p. 191-192
biog. p. 185
ind. tent., gr. tent., bibliog. p. 186-190
Duits
Engels
Exhibition. Micha Ullman. Museum Wiesbaden. 2003.
Keywords: Ullman, Micha